Periodontal condition in Japanese coronary heart disease patients: A comparison between coronary and non‐coronary heart diseases. (18th November 2018) - Aoyama, Norio; Kobayashi, Naho; Hanatani, Tomoya; Ashigaki, Norihiko; Yoshida, Asuka; Shiheido, Yuka; Sato, Hiroki; Takamura, Chisato; Yoshikawa, Shunji; Matsuo, Katsuhiko; Izumi, Yuichi; Isobe, Mitsuaki
Abstract : Objective: The aim of this clinical trial was to assess the relationship between periodontal bacterial burden and coronary heart disease (CHD) in Japanese population. Background: Many epidemiological reports suggest that periodontitis is a risk factor for CHD; however, the influence of each periodontal bacterium and periodontal condition in Japanese CHD patients is unclear. Methods: We studied 897 patients with cardiovascular diseases in Tokyo Medical and Dental University Hospital from May 2012 to August 2015. The subjects were divided into six groups according to age and the existence of CHD (46‐60 years with CHD (n = 56): Group YC, 61‐70 years with CHD (n = 106): Group MC, over 70 years with CHD (n = 177): Group EC, 46‐60 years without CHD (n = 152): Group YN, 61‐70 years without CHD (n = 216): Group MN, and over 70 years without CHD (n = 190): Group EN). Results: We found that the patients in Groups MC and EC had deeper periodontal pocket compared to the patients in Group YN ( P < 0.05), although there was no statistical difference of pocket depth between Group YC and Groups MC and EC. Many subjects in Group EC had high anti‐ Porphyromonas gingivalis and anti‐ Prevotella intermedia antibodies in comparison to Group EN ( P < 0.05). The CHD patients generally had worse oral condition than the non‐CHD patients. Elderly with CHD had a higher level of serum anti‐ Porphyromonas gingivalis antibody and anti‐ Prevotella intermedia antibody than those without CHD. Conclusion: Increased periodontal infection was found in Japanese CHD patients compared to non‐CHD patients.